Pediatric Type 1 Diabetes: Reducing Admission Rates for Diabetes Ketoacidosis. Issue 4 (October 2016) - Ilkowitz, Jeniece Trast; Choi, Steven; Rinke, Michael L.; Vandervoot, Kathy; Heptulla, Rubina A.
Abstract : Background: Diabetes ketoacidosis (DKA) is a life-threatening complication of type 1 diabetes mellitus (T1DM). Reducing DKA admissions in children with T1DM requires a coordinated, comprehensive management plan. We aimed to decrease DKA admissions, 30-day readmissions, and length of stay (LOS) for DKA admissions. Methods: A multipronged intervention was designed in 2011 to reach all patients: (1) increase insulin pump use and basal-bolus regimen versus sliding scales, (2) transform educational program, (3) increased access to medical providers, and (4) support for patients and families. A before-after study was conducted comparing performance outcomes in years 2007-2010 (preintervention) to 2012-2014 (postintervention) using administrative data and Wilcoxon rank sum and Fischer exact tests. Results: DKA admissions decreased by 44% postintervention (16.7 vs 9.3 per 100 followed patient-years; P = .006), unique patient 30-day readmissions decreased from 20% to 5% postintervention ( P = .001), and median LOS significantly decreased postintervention ( P < .0001). Although not an original goal of the study, median hemoglobin A1C of a subset of the population transitioned from sliding scale decreased, 10.3% to 8.9% ( P < .02). Conclusions: When clinical and widespread program interventions were used, significant reductions in DKA hospitalizations, 30-day readmissions, and LOS occurred for pediatric T1DM. Continuous performance improvement efforts are needed for improving DKA outcomes.